Asymptotic and Oscillatory Analysis of Second-Order Differential Equations with Distributed Deviating Arguments - Zuhur Alqahtani; Belgees Qaraad; Areej Almuneef; Higinio Ramos (Mathematics)
This paper focuses on studying the oscillatory properties of a distinctive class of second-order advanced differential equations with distributed deviating arguments in a noncanonical case. Utilizing the Riccati method and the comparison method with first-order equations, in addition to other analytical methods, we have established criteria to test whether the solutions of the studied equation exhibit oscillatory behavior. To verify the validity of the results we obtained and determine their applicability, we present some examples to confirm the strength and accuracy of our proposed criteria.